The Role of Ginger in Cognitive and Antidepressant Function: A Preliminary Exploration of the Effect of Added Sugars - Jennifer Mariza Lynn; Budi Widianarko; Mellia Harumi (JFCN: Journal of Food, Culinary, and Nutrition, 2025)
Ginger offers antioxidant, anti-inflammatory, and neuroprotective properties that can enhance cognitive function and act as an antidepressant. However, excessive sugar intake has been linked to cognitive decline and mental health issues. This review explores the role of added sugar on ginger's ability to improve cognitive function and be an antidepressant. This review is a narrative review that utilizes data collected from various sources of relevant scientific literature spanning from 2014 to 2024. The literature search used online databases and search engines with predetermined keywords. Relevant articles were then selected in two stages. The first selection stage was done by looking at the article's suitability based on the title, keywords, and abstract. The second stage was conducted based on predetermined inclusion and exclusion criteria. The research design includes a comprehensive analysis of the role of ginger and sugar and their combination in cognitive function and antidepressant effects. The findings indicate that many sweet ginger products contain high sugar levels, which can reduce ginger’s antioxidant effectiveness and increase oxidative stress. Furthermore, sugar may raise inflammation and amyloid-beta levels, potentially increasing Alzheimer's risk. In conclusion, while ginger holds significant promise for enhancing cognitive function and mood, the adverse effects of added sugar may negate these benefits.